RDB2OL AND RDB2FFILR: A LANGUAGE AND TOOL FOR MAPPING RELATIONAL DATABASES TO FAST HEALTHCARE INTEROPERABILITY RESOURCES - Indrawan Madda, Wawan
Fast Healthcare Interoperability Resources (FHIR) is a standard for electronically exchanging healthcare information. To use FHIR, implementers must map their data to exchangeablebuilding blocks known as resources. Since many healthcare-related applications rely on relational databases, it becomes necessary to transform data from such databases into the FHIRformat. However, current tools like the Digital Curation Tool (DCT) only support some FHIR resource types and lack support for FHlR extension. The Clinical Asset Mapping Program for FHIR (CAMP FHIR) also lacks support for visualized mapping, requires extra database space, and requires modifying the tool source code when dealing with additional FHIR elements. To avoid modifying the tool source code, a mapping language is needed, but current mapping lang·uages lack support for user-defined programming language code to farther extend capabilities in data preprocessing. To address these issues, we aimed to create a mapping tool named Relational Database To FHlR (RDB2FHIR) and a mapping language named Relational Database To Object (RDB2O,L) which is generated by RDB2FHIR. We conducted validation tests using FHIR examples, and out of 2911 examples, 2910 successfully passed the validation test. Furthermore, we demonstrated the mapping process from a relational database to FHIR using RDB2FHIR and CAMP FHIR and compared them. The results show that RDB2FHIR outpe,forms CAMP FHJR in terms of space usage, mapping visualization, execution of user defined Python code in the mapping langua,ge and support for the FHIR extension without the need to modify the tool source code. Our research success.fully addressed the need for user-defined programming code in the mapping language by creating RDB2OL which is new in FHIR mapping domain. Additionally, our research addressed the aforementioned problems in the mapping tool by creating RDB2FHJR.